Revisiting the Influence of Lending Rate to Indonesia’s Credit Market - Luviyanto, Afif Narawangsa; Prabowosunu, Mohammad Alvin; Pavayosa, Erin Glory (Otoritas Jasa Keuangan, 2025)
This paper investigates the responsiveness of credit volumes to changes in lending rates in Indonesia and reexamines the strength of the monetary transmission mechanism through the credit channel. Using a vector autoregression framework applied to disaggregated bank credit data by sector, loan type, and firm size, we analyse how policy-driven interest rate movements propagate into actual lending outcomes. The results reveal a markedly uneven transmission: credit to micro, small, and medium enterprises (MSMEs) shows negligible sensitivity to interest rate changes, whereas lending to large firms responds more appreciably. In particular, bank credit to large corporates declines significantly when policy rates rise, consistent with conventional theory, while credit to smaller firms remains largely unaltered. These findings suggest that the traditional interest rate pass-through is fragmented and weak in key segments of the economy, undermining the efficacy of pricebased monetary policy. The analysis points to structural factors, including heterogeneous bank behaviour, borrower constraints, and a propensity of banks to shift toward safer assets in uncertain times as underlying causes. The findings imply the need for a more nuanced policy approach that complements interest rate adjustments with targeted interventions to achieve broad-based credit stimulus and effective monetary control.